A Flexible Amorphous Silicon Photovoltaic Module for Portable Electronics - Vygranenko, Yuri (2017)
This article reports on a monolithic 10 cm × 10 cm area PV module integrating an array of 72 a-Si:H n-i-p cells on a thin polyethylene-naphtalate substrate. The design optimization and device performance analysis are performed using a two-dimensional distributed circuit model of the photovoltaic cell. Experimental results show that the shunt leakage is one of the factors reducing the device performance. Using the LBIC technique, the multiple micro-shunts in the n‑i‑p cell were detected. The mechanism of electrical shunts formation is proposed and discussed.